STRUKTUR MIKROANATOMI GINJAL MENCIT (Mus Musculus L.) BETINA SETELAH PAPARAN EKSTRAK ETANOL DAUN MIMBA (Azadirachta indica A. Juss) - Elsa Billah Septiva; Agung Janika Sitasiwi; Sri Isdadiyanto (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2019)
Neem leaves (Azadirachta indica A. Juss.) contain organic compounds such as alkaloids, steroids, flavonoids, triterpenoids, saponins and tannins which have any potency as traditional medicinal. This study aimed to examine the ethanolic extract of Neem leaves on kidney microanatomy in mice (Mus musculus L.). Completely Random Design consists of 4 treatments, 5 replications, namely K (aquadest), P1, P2 and P3 (Treated by dosages 8.4; 11.2 and 14 mg/kg BB/day). The treatments were given orally with volume 0.2 mL for 21 days. Kidney organ was isolated, weighed and made by histological processed with a 5 μm incision thickness using the paraffin method with Hematoxylin-Eosin staining. Observation of preparations were carried out to calculate glomerular diameter, Bowman’s capsule diameter and Bowman’s space diameter. The data were analyzed using ANOVA test at 95% confidence level and continued with DMRT test. The analysis results showed that there was significant affect (p<0.05) on exposure ethanolic extract of Neem leaves to the glomerular and Bowman's capsule diameter but didn’t show significantly affect (p>0.05) to the Bowman's space diameter, changes in kidney weight and drinking consumption of mice. It could be concluded that the exposure of ethanolic extract of Neem leaves in a period of 21 days is still safe to use as traditional alternative medicine. Keywords: Glomerular diameter, kidney weight, Neem leaves